Salary Inequality in Public Services in Chile: A Case Study National Customs Service of Chile - Viera Castillo, Daniel Omar (2019)
The goal of this paper is to analyze remunerations by sex, to determine the gap and discrimination that exists in public entities as in the case of Customs of Chile. The structure of occupational estates and labor income is analyzed through the functional relationships of the Mincer equation. The results indicate that there are wage differences by sex in favor of men of the order of 42%, with professional and technical professionals presenting the greatest inequalities. In addition, married men have higher salaries than women for the same years of experience. These results contrast to the official publications in Chile for the public sector where the wage gap is 27.4%.